2002
DOI: 10.1128/iai.70.8.4609-4620.2002
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium necrophorumLeukotoxin Induces Activation and Apoptosis of Bovine Leukocytes

Abstract: Fusobacterium necrophorum, a gram-negative, rod-shaped, anaerobic bacterium, is a primary or secondary etiological agent in a variety of necrotic, purulent infections in humans and animals. Its major virulence factor is leukotoxin, a high-molecular-weight secreted protein, primarily toxic to ruminant leukocytes. In this study, bovine peripheral blood leukocytes were exposed to various concentrations of immunoaffinity-purified leukotoxin and the cytotoxicity was analyzed by flow cytometry and scanning and trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
43
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 39 publications
1
43
0
1
Order By: Relevance
“…Roberts (321) was first to document a leukotoxin activity in F. necrophorum. Since then the nature and action of the toxin have been fully characterized (282,284,374). Several studies have shown a correlation between virulence and leukotoxin production (99,126).…”
Section: Bacterial Virulence Factorsmentioning
confidence: 99%
“…Roberts (321) was first to document a leukotoxin activity in F. necrophorum. Since then the nature and action of the toxin have been fully characterized (282,284,374). Several studies have shown a correlation between virulence and leukotoxin production (99,126).…”
Section: Bacterial Virulence Factorsmentioning
confidence: 99%
“…Like its relative F. necrophorum, F. nucleatum possesses many virulence factors, such as porin, other outer membrane proteins, and a potent lipopolysaccharide (6,65). Further, toxic metabolites, e.g., butyrate, propionate, and ammonia, are considered to be important in the virulence of these organisms (33,50,57). In concert with other pathogenic bacteria, F. nucleatum appears to play an important part in the destruction of periodontal tissue (7,18).…”
mentioning
confidence: 99%
“…In any of the scenarios the decisive determinant of cell behavior is the signaling system that is activated in the host cell upon infection (19,39,42,58). For instance, a specific leukotoxin produced by F. necrophorum induces signaling for apoptosis in neutrophils (50). F. nucleatum does not express a true leukotoxin, but it can adhere to epithelial cells and invade them by exploiting the cell signaling and the cytoskeletal elements of the host cells (26,28,51,73).…”
mentioning
confidence: 99%
“…16 Fusobacterium isolates were grown in prereduced anaerobically sterilized brain-heart infusion at 37°C to an absorbance of 0.7-0.8 at 600 nm, placed on ice, and pelleted by centrifugation at 10,000 × g for 10 min at 4°C as previously described. 25 Supernatants were filter sterilized with 0.22-μm membrane filters and stored at −80°C.…”
Section: Leukotoxicity Assay By Flow Cytometrymentioning
confidence: 99%